Penerapan Sistem Informasi E-Raport pada Sekolah di Kota Tangerang - Baby Novega Aprilianti; Faysa Permata Rhahmadiahti; Bella Eka Setianingrum; Indah Agustin Pradana; Yayuk Wulandari; Irvan Arif Kurniawan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2023)
Currently information technology has experienced rapid development so that information can be accessed quickly. One of the applications of technology in education today is the existence of an internet-based information system for report card grades or what we usually know as online report cards. This has changed the pattern of society in various aspects, especially the world of education. The e-Raport system is used as an information system designed by schools to inform parents of student progress, which has been implemented in almost all schools in Tangerang City. For example, SMPN 8 Tangerang City is one of the public schools in Tangerang City which uses the e-Raport System as a substitute for manual student learning outcomes reports. The problems raised were the teacher's lack of understanding in accessing e-reports when inputting grades and the lack of understanding of parents in accessing e-reports to see children's development. This research is a literature study that aims to collect information related to the use of online report card information systems implemented by several schools, the results obtained from this literature study are that the online report card system makes it easy for educators to process student value data that can be accessed both by students and parents.